Interference mitigation in indoor multi-cell visible light communication system - Gun, Yip Chuan (2018)
Conventional lighting using incandescent and fluorescent lamps are expected to be gradually replaced by high efficiency light emitting diode (LED) lighting due to the benefits of low power consumption and long-life time. When visible light communication (VLC) is integrated with LED lighting, it becomes a reliable technology in wireless communication. In this project, the integrated system not only can transmit high speed signals but also provide illuminance in indoor environment. The main objective of VLC systems is to obtain maximum performance with minimum interference. Although one of the advantages of indoor VLC is low interference due to the presence of wall, multiple of cells will interfere with each other within a room as illumination requires overlap of luminaries’ emissions [18]. Thus, the approach of this project is to carry out simulations to analyse and compare the results obtained after applying precoding in mitigating inter-cell interference. There are also simulations and discussions on the causes of inter-cell interference, and how the inter-cell interference affects the system performance. The precoding being used to mitigate inter-cell interference are Zero Forcing (ZF) and Minimum Mean Square Error (MMSE). We apply two types of precoding at the transmitter of the VLC system for downlink transmission. After multiple trial and errors in simulations, it is found that the proposed precoding can be one of the choices to provide better performance in optical wireless communication as well as high data rate. Based on a set of numerical results, the performance advantages due to the proposed coordination and precoding designs are presented.